PENGGUNAAN METODE PEMBIASAAN DALAM MENINGKATKAN HAFALAN SURAH PENDEK PADA MATA PELAJARAN AL-QUR’AN HADIST DI KELAS 1 MIN 2 SAMBAS TAHUN PELAJARAN 2023-2024 - Parni Parni; M. Sabiqul Huda; Rika Afani (CV. Adiba Aisha Amira, 2026)
The purpose of this study is to explain: 1). The ability to memorize short surahs in the Al-Qur’an and Hadith subject among first-grade students of MIN 2 Sambas. 2). The implementation of the habituation method in improving the memorization of short surahs in the Al-Qur’an and Hadith subject among first-grade students of MIN 2 Sambas. 3). The implications of the habituation method in improving the memorization of short surahs in the Al-Qur’an and Hadith subject among first-grade students of MIN 2 Sambas. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The validity of the data was examined using triangulation and member checking. The results of the study show that: 1. The ability to memorize short surahs in the Al-Qur’an and Hadith subject among first-grade students of Madrasah Ibtidaiyah Negeri 2 Sambas includes: a) ability, b) memorization, c) sources of motivation, d) development, e) improvement, f) prevention, and g) habituation. 2. The implementation of the habituation method in improving the memorization of short surahs in the Al-Qur’an and Hadith subject among first-grade students of Madrasah Ibtidaiyah Negeri 2 Sambas consists of: a) routine activities, b) spontaneous activities, c) exemplary behavior (role modeling), and d) programmed activities. 3. The implications of the habituation method in improving the memorization of short surahs in the Al-Qur’an and Hadith subject among first-grade students of Madrasah Ibtidaiyah Negeri 2 Sambas include: a) enabling children to memorize independently in their daily lives without parental assistance, b) internalized values that are manifested in their lives, c) application in daily life, and d) habituation can encourage and accelerate behavioral change.